Penerapan Model Pembelajaran Project Citizen untuk Meningkatkan Keterampilan Berpikir Kritis dan Kreatif Siswa - Luqman Luqman (Faculty of Education Universitas Negeri Malang, 2017)
Abstract: The purpose of this study are: (1) to describe the application of the instructional model of project citizen to improve the ability of critical and creative thinking; (2) to know the improvement of critical thinking ability by applying the instructional model of project citizen; and (3) to know the improvement of creative thinking ability by applying the instructional model of project citizen. This study uses a classroom action research design (PTK). The subjects of the study were 5th grade students of SD Negeri Sabilillah Malang. The research data were obtained from: observation of teacher activity; observation of student activities; and analysis of student learning outcomes. The results concluded that the application of the instructional model of project citizen can improve critical thinking skills and creative, which is done through six steps, namely: identify problems; choose a problem; collect information; developing portfolio; presents portfolio; and reflection on the learning experience. Application of the instructional model of project citizen can improve critical thinking skill, that is Cycle I equal to 74.3 to 83.9 in Cycle II. In addition, the application of the instructional model of project citizen can also improve the skills of creative thinking, which is Cycle I of 70.8 to 75.6 in Cycle II.Abstrak: Tujuan dari penelitian ini adalah: (1) mendeskripsikan penerapan model pembelajaran project citizen untuk meningkatkan kemampuan berpikir kritis dan kreatif; (2) mengetahui peningkatan kemampuan berpikir kritis dengan menerapkan model pembelajaran project citizen; dan (3) mengetahui peningkatan kemampuan berpikir kreatif dengan menerapkan model pembelajaran project citizen. Penelitian ini menggunakan desain penelitian tindakan kelas (PTK). Subjek penelitian adalah siswa Kelas 5 SD Negeri Sabilillah Malang. Data penelitian diperoleh dari: pengamatan kegiatan guru; pengamatan kegiatan siswa; dan analisis hasil belajar siswa. Hasil penelitian menyimpulkan bahwa penerapan model pembelajaran project citizen dapat meningkatkan keterampilan berpikir kritis dan kreatif, yang dilakukan melalui enam langkah, yaitu: mengidentifikasi masalah; memilih masalah; mengumpulkan informasi; mengembangkan portofolio; menyajikan portofolio; dan refleksi pada pengalaman belajar. Penerapan model pembelajaran project citizen dapat meningkatkan keterampilan berpikir kritis, yaitu Siklus I sebesar 74,3 menjadi 83,9 pada Siklus II. Selain itu, penerapan model pembelajaran project citizen juga dapat meningkatkan keterampilan berpikir kreatif, yaitu Siklus I sebesar 70,8 menjadi 75,6 pada Siklus II.